Strategi Penguatan Produk Lokal Tanjak dalam Meningkatkan City Branding di Kota Palembang - Grasopa, Nadelia; Novia Kencana; Isabella (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2024)
The aim of this research is to determine the strategy for strengthening local Tanjak products as well as the obstacles or obstacles to the strategy of strengthening local Tanjak products in improving city branding in Palembang City. The method used in this research is a qualitative method with a case study approach. The unit of analysis in this research is the Palembang City Tourism Office with a total of seven research informants. The qualitative data analysis used is Creswell qualitative analysis. The results of this research indicate that the strategy of strengthening local Tanjak products carried out by the Regional Government in order to improve the city branding of the City of Palembang has gone well, as can be seen from the indicators of the city branding development strategy which has supported this strategy well. These indicators are internal factors, consideration of external conditions and communication strategies used to strengthen local products. The obstacle or obstacle faced in the process of strengthening local Tanjak products is that the use of digital media, especially in the era of society 5.0, has not been used optimally by local governments to introduce and promote Tanjak to the public. Apart from that, the regional government budget for building Tanjak ornaments on agency buildings in South Sumatra is still inadequate and ASN's consistency in using Tanjak during working hours determined by the Palembang City government is still not running well.